Penggunaan Artificial Intelligence dalam Pembelajaran PAI di SMP Darul Falah Al-Haqiqiyah: Studi Kualitatif tentang Peluang, Risiko, dan Etika - Fauzi Fauzi (STIT Al-Ittihadiyah Labuhanbatu Utara, 2026)
Although the use of Artificial Intelligence (AI) in education has been widely researched, specific studies on AI in Islamic Religious Education (PAI) learning at the junior high school level, particularly regarding opportunities, risks, and ethics, are still very limited. This study aims to analyze the use of AI in Islamic Religious Education (PAI) learning at Darul Falah Al-Haqiqiyah Junior High School based on the experiences of teachers and students. The method used is descriptive qualitative with a field study design. The research informants consisted of Islamic Religious Education teachers and students who were selected purposively. Data were collected through observation, interviews, and documentation, then analyzed using data reduction, data presentation, and conclusion drawing techniques. The results of the study generally indicate that AI has great potential to increase learning efficiency, expand access to learning resources, and support student independence. However, AI also carries significant risks such as instant dependency, bias in religious information, and the potential degradation of learning ethics if without teacher guidance. In conclusion, AI should be positioned proportionally as a tool, not a substitute for teacher figures or authoritative sources of Islamic law. The main contribution of this study is to provide an empirical and contextual overview of the dynamics of acceptance, real challenges, and ethical responses of teachers and students to AI in Islamic Religious Education classrooms. These results can serve as a foundation for education practitioners in understanding the digital reality in Islamic-based schools.